Psychological time of green entrepreneurs: a mixed methods study of SMEs - Zabelina, Ekaterina (2023)
Purpose: Green entrepreneurship is a topic of transcendental importance for today's societies. Studies on why entrepreneurs engage in green business have primarily focused on external influences, paying little attention to internal factors such as cognitive mechanisms. This study aims to fill this gap by focusing on the characteristics of the perceived (psychological) time of entrepreneurs who choose green businesses. Design/methodology/approach: Using a sequential exploratory mixed methods design, this study conducts a series of 20 in-depth interviews with green entrepreneurs in Russia, an emerging economy, and then formulates the hypotheses. The hypotheses are tested in the quantitative phase by surveying 389 green and non-green entrepreneurs. Findings: The data obtained in the survey phase support several hypotheses. Specifically, green entrepreneurs think more critically about their past than their non-green colleagues. Similarly, green entrepreneurs have a longer time perspective and are more focused on possible future events. Finally, green entrepreneurs are farsighted and perceive the future more negatively than non-green entrepreneurs. Research limitations/implications: The data obtained in the survey phase support several hypotheses. Compared with non-green entrepreneurs, green entrepreneurs think more critically about their past, have a longer time perspective and are more focused on possible future events. In addition, green entrepreneurs are farsighted and perceive the future more negatively than their non-green counterparts. Originality/value: This study contributes to the least examined area in the relevant literature by identifying internal factors that explain green entrepreneurship. Furthermore, to the best of the authors’ knowledge, it is one of the first to provide an in-depth understanding of the characteristics of the perceived (psychological) time of green entrepreneurs. © 2023, Emerald Publishing Limited.